Wastewater treatment of biodiesel production using persulphate ion as an oxidant. - Maria Teresa Borralho; Ana Pardal; Solange Coelho (Instituto Politécnico de Viseu, 2019)
Introduction: The production of biodiesel produces a highly polluting effluent, because presents high values of Chemical Oxygen Demand (COD), oils and fats, among other contaminants. Sodium persulphate is a powerful oxidant (Eº = 2.1V). In addition to the direct oxidation that is favored in alkaline media, it can be induced by photolytic processes, catalytic and / or catalytic photos forming sulphate radicals (Eº = 2.6 V) thus providing reaction mechanisms with free radicals like hydroxyl radicals. Methods: In this work the effect of the potassium monopersulphate compound (2KHSO5.KHSO4K2SO4), (Oxone) on the removal of COD in residual water from the biodiesel purification step was tested. Results: The tests, direct oxidation at alkaline pH and catalytic oxidation with cobalt ions, Co(II), showed that the former, for Oxone concentrations of 1.00x10-2 M and 4.00x10-3 M, were not effective because no decomposition occurred, for reaction times over three hours, thus not occurring removal of COD. In the catalytic assays combinations were tested, varying between 5.00x10-3 M and 7.50x10-2 M for the oxidant and 0.10 μM and 1.00 μM for the catalyst. The complete decomposition of the oxidant was always verified between 15 min. and 2 h. The tests with the lowest concentration of cobalt showed COD removal rates around 20% and the highest one reached 60%.  Conclusions: The most favorable assay achieves significant COD removals, but not enough for the effluent to be discharged in the hydric medium according the portuguese legislation.